Razumeti "novi konfucianizem" - Bueno, André (Ars et humanitas, 2016)
Th is article focuses on an important change in Chinese thinking of the 20th century: the rebirth of Confucianism as the intellectual movement called "New Confucianism" which is considered in the China of today to be a possible substitute for Marxist ideology. But what exactly is the "New Confucianism"? Th e author fi rst attempts to highlight the defi nition of Confucianism from the Western perspective and the problems that arise in that process. Th e study is based primarily on the work of Jiang Qing, one of the principal thinkers of this movement of ideas, and on the analysis of the main western interpreter of Qing, researcher Daniel Bell. Further along, the paper discusses some of the most common tags of this movement: New Confucianism as a religion, as a social doctrine, and as a new political option for the future. Notwithstanding the elusiveness of the concept it appears to be the case that this movement is developing spontaneously in modern Chinese society and is gaining more and more followers, even via a lighter literary genre through which modifi ed Confucian thoughts and tips for coping with everyday life can approach a wider crowd.
Keywords: družbene doktrine; kitajska filozofija; novi konfucianizem; politika; religija